British Labour Party papers, 1968-1994. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2005)
The Parliamentary Labour Party is the organisation of Labour members of Parliament (MPs) founded in 1906. Included in this collection are all the minutes of the Party Meetings, the Liaison Committee and the Parliamentary Committee (Shadow Cabinet) for the period 1968-1994. This period represents a turbulent one in British politics, during the early part of which Labour were twice in power. It begins with the latter half of a Labour government under Harold Wilson, followed by the Conservative government of Edward Heath, which brought Britain the three-day week and into the EEC. Less than a year after Labour returned to power in 1974 following a hung parliament, the Conservative Party elected a new leader. The Margaret Thatcher years appear in their entirety, including the Falklands War and the miners' strike. In the Labour Party, leadership moved from Jim Callaghan to Michael Foot to Neil Kinnock. Initially policy shifted to the left. However, after the Party's heavy defeat in the election of 1983, the concept of New Realism" started to emerge. In its wake came Tony Blair, whose progress to the top is charted by these papers, which culminate in Margaret Beckett's caretaker leadership after the death of John Smith. This span from the papers of the PLP is published with a short online guide by Stephen Bird, former archivist at the Labour History Archive and Study Centre, Manchester.
Date range: 1968-1994.
Keywords: Labour Party (Great Britain) -- History